The Evolution of Ronald Dworkin's Legal Philosophy: From Interpretivism to Integrity - Asa, Agam Ibnu (Abjad Journal of Humanities & Education, 2025)
Ronald Dworkin's legal philosophy marked a paradigm shift from positivism, emphasizing law as a deep interpretive practice. The problem addressed is the lack of systematic exploration into the evolution of Dworkin's thought from early interpretivism to integrity and the unity of value as a single narrative. This study aims to trace how Dworkin's ideas developed and shaped each other. Through literature review and conceptual analysis of his major works, this research finds that Dworkin's early interpretivism, which focused on criticizing Hart and the role of principles in "hard cases," developed and influenced the formation of the theory of "Law as Integrity" by demanding principled coherence. Key stages in his evolution include the critique of positivism, the development of rights as trumps, the formulation of integrity as a legal virtue, and the introduction of the unity of value. Furthermore, the concept of "unity of value" strengthens the theories of integrity and interpretivism by providing a philosophical foundation that moral values are fundamentally coherent. In conclusion, Dworkin built an integrated philosophical architecture, asserting law as an ongoing moral project aimed at realizing justice and principled consistency.